Changing Boundaries in the Americas. New Perspectives on the U.S-Mexican, Central American, and South American Borders - Méndez Mungaray, Elizabeth (Frontera Norte, 2017)
Lawrence A. Herzog, San Diego, University of California, Center for U.S.Mexican Studies, 1992